Primary school children’s oral hygiene knowledge assessed with different educational methods: a cross-sectional study - Canan Bayraktar Nahir; Alem Coşgun; Necibe Damla şahin; Halenur Altan (BMC Oral Health)
Abstract Background Different educational methods play an important role in oral hygiene education programs. This study aims to evaluate the impact of various educational methods on the oral hygiene knowledge of primary school children. Methods A total of 490 primary school students participated in this cross-sectional study. The students were assigned to one of three groups: a verbal explanation group, an animation group, or a peer-led reels group. Before and after the intervention, the students completed questionnaires assessing their oral hygiene knowledge. Results A significant increase was observed in the post-educational knowledge levels of the children in three educational methods (p < 0.001). The study found that the main effect of educational methods was statistically significant (p < 0.001). However, effects of gender, and tablet/mobile phone use, respectively, were not statistically significant (p = 0.694, p = 0.641). The animation group (6.73) and the verbal expression group (6.57) had the highest post-training knowledge levels, respectively, while the peer-led reels group had the lowest (5.95) (p < 0.001). Conclusions All three educational methods are effective in promoting oral hygiene, but due to the accessibility and consumption of information in the current technological era, animation videos may be more useful and suitable for modern education. Trial registration ID: NCT06569745; Date: 21.08.2024; ‘retrospectively registered’.